The beneficial effect of natural antioxidants from olive oil with fig and date palm fruit extracts on biochemical and hematological parameters in rats during diethylnitrosamine-induced carcinogenesis - Abdallah H. Fathy; Mohamed A. Bashandy; Samir A. Bashandy; Ahmed M. Mansour (Canadian Science Publishing, 2018)
Diethylnitrosamine (DEN) is a well-known carcinogen. The aim of our study was to determine the role of olive oil (7 g/kg) with fig (1 g/kg) (OF) and (or) date palm (1 g/kg) (D) fruit extracts during DEN treatment of male Wistar rats. The OF-DEN and (or) D-DEN groups were given oral antioxidants daily for two weeks before and during DEN treatment (21 weeks). The DEN-treated group showed dramatic results for all investigated parameters as compared with the control rats. All OF-DEN and D-DEN groups showed significant improvement in hepatic thiobarbituric acid reactive substances, reduced glutathione, and nitric oxide concentration in the liver tissue, in addition to improvement in serum vascular endothelial growth factor level, alpha-fetoprotein, lipid profile, lipid risk ratios, and the hematological parameters as compared with the DEN-treated group. In conclusion, the administration of OF and (or) D fruit extracts to DEN-treated rats resulted in a considerable improvement in the investigated biochemical and hematological parameters. In addition, the combined OFD treatments showed greater improvements revealing the synergistic effect of the combination.